2016
DOI: 10.1038/srep28051
|View full text |Cite
|
Sign up to set email alerts
|

Morphology evolution and pure red upconversion mechanism of β-NaLuF4 crystals

Abstract: A series of β-NaLuF4 crystals were synthesized via a hydrothermal method. Hexagonal phase microdisks, microprisms, and microtubes were achieved by simply changing the amount of citric acid in the initial reaction solution. Pure red upconversion (UC) luminescence can be observed in β-NaLuF4:Yb3+, Tm3+, Er3+ and Li+ doped β-NaLuF4:20% Yb3+, 1% Tm3+, 20% Er3+. Based on the rate equations, we report the theoretical model about the pure red UC mechanism in Yb3+/Tm3+/Er3+ doped system. It is proposed that the pure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 53 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…NaLuF 4 -based UCNCs have been demonstrated to exhibit bright upconversion luminescence (UCL) [17,18,19,20,21,22,23,24] and show efficient five- and four-photon ultraviolet emissions under continuous wave excitation at 980 nm [25,26,27]. Despite recent success in synthesizing NaLuF 4 nanoplates or nanorods with size over ~30 nm using thermal decomposition method [28,29,30,31] or hydrothermal method [32,33,34,35,36,37,38], the ability to prepare uniform single crystal phase sub-10 nm NaLuF 4 UCNCs remains elusive. Moreover, doping of a high concentration of inert Gd 3+ ions (≥20%) was typically required to prepare small-sized monodisperse NaLuF 4 UCNCs with single crystal phase previously [17,39], thus delivering traits actually from an entity of Lu-Gd alloyed host.…”
Section: Introductionmentioning
confidence: 99%
“…NaLuF 4 -based UCNCs have been demonstrated to exhibit bright upconversion luminescence (UCL) [17,18,19,20,21,22,23,24] and show efficient five- and four-photon ultraviolet emissions under continuous wave excitation at 980 nm [25,26,27]. Despite recent success in synthesizing NaLuF 4 nanoplates or nanorods with size over ~30 nm using thermal decomposition method [28,29,30,31] or hydrothermal method [32,33,34,35,36,37,38], the ability to prepare uniform single crystal phase sub-10 nm NaLuF 4 UCNCs remains elusive. Moreover, doping of a high concentration of inert Gd 3+ ions (≥20%) was typically required to prepare small-sized monodisperse NaLuF 4 UCNCs with single crystal phase previously [17,39], thus delivering traits actually from an entity of Lu-Gd alloyed host.…”
Section: Introductionmentioning
confidence: 99%
“…If the emission intensity ratios from the 2 H 11/2 and 4 S 3/2 is adjusted, the temperature sensitivity will change greatly. As reported that the energy gaps between 3 F 4 and 3 H 6 of Tm 3+ ion, as well as between 5 I 7 and 5 I 8 of Ho 3+ ion, were equal to the energy gap between 2 H 11/2 and 4 F 9/2 of Er 3+ ion 19 . Thus, the population of 2 H 11/2 and 4 S 3/2 levels of Er 3+ can be adjusted through the cross relaxation energy transfer between Er 3+ and Tm 3+ (or Ho 3+ ).…”
Section: Introductionmentioning
confidence: 78%
“…At present, trivalent rare earth ions, such as Er 3+ , Ho 3+ , Tm 3+ , Eu 3+ , and Pr 3+ , have been used as activators to study optical temperature sensing behaviors 13 18 . Among these ions, Er 3+ is preferred for temperature sensing due to the large energy gap (about 800 cm −1 ) and small overlap of the two emission peaks from 2 H 11/2 and 4 S 3/2 levels 19 22 . So the optical thermometry based on up-conversion emission of Er 3+ doped phosphors has been explored in different hosts by using infrared excitation sources 12 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Both the population density and accuracy of the ET1 and ET2 models can be confirmed by rate equations, which have been successfully used to interpret the ET process between Yb 3+ and Er 3+ in several host matrices 34,36,37 . The corresponding rate equations of ET1 and ET2 are shown as Table 1.…”
mentioning
confidence: 85%